Waste Management Policy Innovation in a Sound Governance Perspective - Mujahidin, Deni; Ilhami, Rizky (Yayasan Pendidikan Belajar Berdikari, 2024)
Innovation in good waste management can serve as a springboard for development, affecting many elements of society and the economy. Innovation is the key to good governance. Innovation in policy and administration is critical to good government. Sound governance brings foreign actors into the discussion. This study takes a qualitative approach, employing the Literary Review research method, which is a systematic, explicit, and reproducible procedure for discovering, analyzing, and summarizing research works and ideas generated by researchers and practitioners. Secondary data sources include literature, journal references, and study findings. rubbish management in Indonesia is still deemed unsatisfactory, as seen by the presence of rubbish in numerous cities, as well as isolated sub-districts and villages where there is no method to resolve the waste. It is apparent that waste management policies and strategies have yet to reach the deepest strata of society. To deal with this situation, it is evident that innovation is required. When viewed through the lens of Sound Governance, as a dimension of international or globalization forces, Indonesia must immediately collaborate with countries that excel at waste management; international actors, namely other countries or international institutions such as UNEP, must be involved. As an example of innovation that can be carried out using today's technological advances, consider the installation of incinerators in various villages/subdistricts throughout Indonesia, allowing village/subdistrict governments to manage their respective waste, with environmentally friendly equipment and the ability to process the results. This invention must be promptly declared in a policy so that norms and regulations may be established and executed. Of course, in this scenario, all levels of society must be involved, in order to develop public awareness of trash.